Guru Cermat, Anak Hebat: Peningkatan Kapasitas Guru PAUD melalui Pelatihan Skrining Tumbuh Kembang di TK Muslimat NU 27 Malang - Iftitahurroza, Hilma Tsurayya; Widya Sishartami, Lintang; Ariesaka, Kiky Martha; Weningtyas, Anditri; Kurniawati, Andini; Qurrataa'ayun, Ahmad Al; Aulia, Sabrina; Auliarahama, Zhafirah; Manggolono, Lintang Nirmalasari Gemalochaya (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Early childhood is a golden period of growth and development that serves as the foundation for the quality of human resources in the future. Developmental screening in early childhood is crucial to detect growth and developmental disorders at an early stage. Early Childhood Education (ECE) teachers play a strategic role in conducting screenings within educational institutions. However, limited teacher capacity in performing developmental screenings often becomes a challenge. Methods: The program was conducted using a training approach designed based on the ADDIE model. The effectiveness of the training was evaluated by comparing the participants’ pre-test and post-test scores. Results: The activity was implemented at TK Muslimat NU 27 Malang and was attended by 12 participants, all of whom were PAUD teachers. The results showed a significant improvement in teachers’ knowledge and skills based on pre-test and post-test outcomes, as well as increased confidence in conducting growth and development screening in schools. Conclusion: This activity improved teachers’ capacity in children growth and development screening; however, further monitoring and evaluation of implementation are needed.